2018
DOI: 10.1002/cphc.201800738
|View full text |Cite
|
Sign up to set email alerts
|

Interband Electron Pairing for Superconductivity from the Breakdown of the Born‐Oppenheimer Approximation

Abstract: The origin of interband electron pairing, responsible for enhancing superconductivity, and the factors controlling its strength were examined. We show that interband electron pairing is a natural consequence of breaking down the Born-Oppenheimer approximation during electron-phonon interactions. Its strength is determined by the pair-state excitations around the Fermi surfaces that take place to form a superconducting state. Fermi surfaces favorable for the pairing were found, and the implications of this obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…[36][37][38] Therefore, we evaluate the bulk modulus, shear modulus and the Viker hardness of ice structures Pmc2 1 , P2 1 and C2/m with incremental pressures, according to Eq. (7). With the increase of pressure, the three phases give rise to the repulsion by the valence electrons that come from the core electrons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[36][37][38] Therefore, we evaluate the bulk modulus, shear modulus and the Viker hardness of ice structures Pmc2 1 , P2 1 and C2/m with incremental pressures, according to Eq. (7). With the increase of pressure, the three phases give rise to the repulsion by the valence electrons that come from the core electrons.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2] The electron-phonon mechanism of superconductivity was proposed based on the Bardeen-Cooper-Schrieffer (BCS) theory, [5] which is a single band model and does not take into account the multiband nature of the actual electronic structures. The multiband effect has been previously studied by Suhl et al [6] and Whangbo et al [7] The McMillan equation and its variations are essential empirical relations between critical temperature of superconductor and other parameters such as the effective electron-phonon coupling constant (λ). These equations contain part of the contributions of the multiband effect based on the realistic electronic structures, thereby provide feasible ways for theoretical prediction of superconducting materials and enable recent works of superconductor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a behavior can be considered as the result of the O(2p)/O(2s) hybridization (Figure 6c). This dipole oscillation may contribute, as in atomic spinodes, to induce a decomposition into various components of the e u /b 1 mixtures in equilibrium, exchanging hole pairs, and consequently leading to the Whangbo Hamiltonian of pair-occupied and pair-unoccupied states [23,43].…”
Section: The Double Unit Cell (Cu2o4) 4−mentioning
confidence: 99%
“…These two kinds of electrons interact with phonons in a very different way [20,21], and thus naturally lead to a two-band superconductivity mechanism [22] for conventional superconductors. The inter-band pairing which is important for enhancing T C was shown to be due to the breakdown of the Born-Oppenheimer approximation by Whangbo et al [23]. Recently, Deng et al have shown that the generalized coherent state constructed by pure group theory can be used to describe the superconducting state.…”
Section: General Overviewmentioning
confidence: 99%